PENGARUH PEMBERIAN EKSTRAK ANGKAK TERHADAP KADAR HDL DARAH (Studi Eksperimental pada Tikus Jantan Galur Wistar yang Mendapat Diet Tinggi Lemak) - Edijanti Goenarwo (Majalah Ilmiah Sultan Agung, 2011)
Red yeast rice contains fiber, monakolin-K and other unsaturated fatty acids, which can allegedly be used to prevent coronary heart disease that is triggered by elevated levels of blood cholesterol and low HDL blood. Therefore, to investigate the effect of red yeast rice extract on blood levels of HDL cholesterol in mice that received high-fat diet. This study used a randomized design of post test control group design. The samples used were male rats of wistar strain were 24 tails. In this study there were 4 groups (I, II, III, IV), namely group I only fed with standard (PS), group II was given PS and high-fat diet (DTL), group III was given PS, DTL, and 20 mg of red yeast rice extract group IV were given PS, DTL and 40 mg of red yeast rice extract. Examination of blood HDL levels performed on day 22 of treatment. Data were tested with one-way Anova test followed by LSD post hoc test.The results show average blood levels of HDL cholesterol: the group I amounted to 43.2850 mg / dl, group II of 35.8183 mg / dl, group III of 42.4267 mg / dL and group IV of 48.2467 mg / dl. Having tested with one-way ANOVA test at level of 95% obtained significant results (p <0.05). In post hoc LSD test showed that on average significantly different from group II with group I, III and IV. (P <0.05) while between group I, III and IV obtained results do not differ (p> 0.05).From the results of these studies concluded that administration of red yeast rice extract effect on blood HDL rats fed high-fat diet, and red yeast rice extract 20 mg and 40 mg can raise levels of blood HDL wistar strain male rats fed high-fat diet. KeywordsÂ  :Â  red yeast rice extract, blood HDL levels.